2012
DOI: 10.1007/s12529-011-9215-0
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy Mediates the Associations of Social Support and Depression with Treatment Adherence in Heart Failure Patients

Abstract: Self-efficacy explains the influence of social support and depression on treatment adherence and may be a key target for interventions to improve disease management and self-care behaviors in HF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
143
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(170 citation statements)
references
References 49 publications
16
143
0
4
Order By: Relevance
“…Generally speaking, working on promoting self-efficacy and empowering them is important in self-care regimen follow-up through selfefficacy promotion (13). It is depicted that self-efficacy affects health and health-related outcomes based on the behaviors in treating the patients with chronic diseases and is considered as one of the most significant predictors of behavioral modifications in the patients (4,14,15). On the other hand, self-efficacy is directly associated with healthy behaviors and indirectly influences healthy behaviors to achieve the goals, the challenges the individuals are facing and perseverance, commitment and effort to reach the goal (16).…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, working on promoting self-efficacy and empowering them is important in self-care regimen follow-up through selfefficacy promotion (13). It is depicted that self-efficacy affects health and health-related outcomes based on the behaviors in treating the patients with chronic diseases and is considered as one of the most significant predictors of behavioral modifications in the patients (4,14,15). On the other hand, self-efficacy is directly associated with healthy behaviors and indirectly influences healthy behaviors to achieve the goals, the challenges the individuals are facing and perseverance, commitment and effort to reach the goal (16).…”
Section: Introductionmentioning
confidence: 99%
“…Patients who feel powerless due to the effects of their illness, or who have previously expected healthcare providers to provide the majority of care may be shown to have worse CSE, are more likely to develop poorer coping strategies, and are less likely to make significant changes to their lifestyles following an acute coronary event [11]. Amongst patients with CVD, an individual's attitude towards maintaining a normal level of function and their ability to control symptoms predicts their ability to adhere to diet and exercise regimes in the long term rehabilitation of their illness [12]. A person's confidence in their ability to make changes to their lifestyle, coupled with their perception of barriers to these changes, can significantly impact their ability to adhere to a management plan [13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also shown that patients with a low sense of self efficacy are more likely to have worse health outcomes [12]. Analyses of data from the Heart and Soul study, comprising patients with heart failure (HF), have shown that those with low self efficacy perform worse on four health outcomes of disease specific and general health domains, including a greater symptom burden, greater physical limitation, a worse quality of life and worse overall health [5,16].…”
Section: Introductionmentioning
confidence: 99%
“…We used a meta-analysis methodology to minimize these issues. We conducted a literature review to obtain papers with adherence correlation values and identified a representative sample of 14 papers (Wagner et al, 2011;Holzemer et al, 1999;Gifford et al, 2000;Carrico et al, 2011;Schneider, Kaplan, Greenfield, Li, & Wilson, 2004;Ammassari et al, 2001;Simoni, Frick, & Huang, 2006;Bottonari, Safren, McQuaid, Hsiao, & Roberts, 2010;Grant et al, 2004;Johnson, Elliott, Neilands, Morin, & Chesney, 2006;Wu, Moser, Chung, & Lennie, 2008;Maeda, Shen, Schwartz, Farrell, & Mallon, 2012;Hansen et al, 2009;Stawski, Silwinski, Almeida, & Smyth, 2008). We reserved a statistically rigorous metaanalysis for later studies.…”
Section: Formulationmentioning
confidence: 99%